Problematika Pemilihan Kepala Daerah Dan Wakil Kepala Daerah Secara Langsung Atau Tidak Langsung Dalam Prespektif Demokrasi - Ibnususilo, Efendi (UIR Law Review, 2024)
The election of regional heads and deputy regional heads is one of the things that has sparked attention lately, because the 2024 general elections will soon be held even though the implementation does not coincide with the election of the President and Vice President and the election of legislative members. Nevertheless, there are still many people who compare the election of regional heads and deputy regional heads directly or indirectly considering that the performance results of the regional heads and deputy regional heads have not seen the expected results. In fact, both direct and indirect elections have their own advantages and disadvantages so there is no need to debate because basically both elections are democratic elections